The cross-section of conditional mutual fund performance in European stock markets - Ayelen Banegas; Ben Gillen; Allan Timmermann; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2012)
This paper implements strategies that use macroeconomic variables to select European equity mutual funds, including Pan-European, country, and sector funds. We find that several macro-variables are useful in locating funds with future outperformance, and that countryspecific mutual funds provide the best opportunities for fund rotation strategies using macroeconomic information. Specifically, our baseline long-only strategies that exploit time-varying predictability provide four-factor alphas of 12-13%/year over the 1993-2008 period. Our study provides new evidence on the skills of local versus Pan-European asset managers, as well as how macroeconomic information can be used to locate and time these local fund manager skills.
Keywords: G11; G15; G23; 330; European equity markets; mutual fund performance; time-varying investment opportunities